Pengaruh Komunikasi Kelompok Terhadap Pemahaman Materi Mata Kuliah Analisis Kebijakan Pendidikan Islam - Nanda Choirun Nisa'; Dewi Putri Nur Aini; Alfian Ichsan Subekti; Fathur Rahman Arrozi; Muhammad ‘Izzul Muqorrobin (IAINU Kebumen, 2023)
The purpose of this research is to find out whether there is an effect of group communication on the understanding of the material for the Islamic Education Policy Analysis course. This study uses a quantitative research type. The sample in this study were D2 PGMI class students Class of 2020 at Kiai Haji University Achmad Siddiq Jember. Respondents in this study consisted of 5 men and 25 women. Collecting data used in this study using a research questionnaire. The type of data in this study is a Likert scale. The analysis in this study used validity and reliability tests as well as simple linear regression analysis with the help of Microsoft Excel. The results showed that 1) F count = 4.327 > F table = 1.701 or sig F = 0.046 < alpha = 0.05, then Ha is accepted which means there is a significant influence between group communication and understanding of Islamic Education Policy Analysis material. 2) Based on the data from simple linear regression analysis, it shows that the correlation value between x and y is 0.3658 which is included in the low category and the results of the data on the value of determination show the percentage of influence of group communication on the understanding of the material for the Islamic Education Policy Analysis course by 10% while the remaining 90% is influenced by other variables not examined in this study. The results of this study indicate that in order to achieve a good understanding of the material, group communication can be used in student learning activities to achieve optimal learning goals.